BISNIS EKSPOR IMPOR Growbox - Elwin Graciano Lay; Fauziah Isnaini; Ketut Sadhunata W.; Maulana Muhammad; Nuriah Nuriah (Journal of The Community Development in Asia, 2018)
This paper is written to find out what is done for the export process of goods. The products exported in this paper are paprikabox products. Paprikabox is a product idea that the author created. In this paper there are some information such as company profiles, product ideas, marketing strategies, export documents and procedures, human resources, and financial. The idea of this paprikabox product will later be submitted to PT. Ideas Indonesia as a reference for new products that will be mass produced. Keywords : Export, Paprika, Paprikabox, Marketing